(untitled) (UNIZIK Journal of STM Education, 2025)
This study investigated the negative influence of Information and Communication Technology (ICT) on the academic performance of junior secondary school students in Nnewi North Local Government Area, Anambra State, Nigeria. A descriptive survey design was adopted, involving 300 students from government-owned secondary schools using convenience and simple random sampling techniques. Data was collected through a self-structured questionnaire which is divided into two sections: one for demographic information and the other for responses. The instrument was subjected to face validation and a pre-test for clarity and accuracy. Its reliability was confirmed using the split-half method. Data were analyzed using frequency percentages, mean, and standard deviation. A decision rule was set: mean scores of 2.5 and above indicated high influence, while scores below 2.5 signified low influence. The findings highlighted several perceived negative effects of ICT on students’ academic performance. These results contribute to understanding the extent of ICT’s adverse impact and provide a basis for developing strategies to reduce its negative effects, ultimately supporting improved academic outcomes in the area.